A further new species of Euphorbia (Euphorbiaceae) from Moçambique - Bruyns, Peter V. (Phytotaxa, 2020)
A small shrubby species, Euphorbia pseudocontorta, belonging to subg. Euphorbia is described from the central part of Moçambique. It is closely related to E. contorta.